Implementation of the Merdeka Belajar – Kampus Merdeka Curriculum in Improving the Readiness of Makassar State University Students to Enter the World of Work and Industry - Aslinda, Andi; Haerul, Haerul; Zainal, Henni; Akmal, Muh Ikramullah; Ibrahim, Ibrahim (International Journal of Education, Management, and Technology, 2025)
This study investigates the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) curriculum at Makassar State University and evaluates its effectiveness in enhancing students’ career readiness. Employing a qualitative descriptive exploratory approach within a case study framework, data were collected through interviews, observations, and document analysis. The analysis followed the interactive model of Miles, Huberman, and Saldana. Findings demonstrate that the eight MBKM programs—Student Exchange, Internship, Teaching Practice, Research, Humanitarian Project, Entrepreneurship, Independent Study, and Thematic Community Service—have significantly bridged the gap between academic learning and real-world professional demands. The MBKM initiatives have enhanced the relevance of academic content and contributed to the development of essential 21st-century soft skills, including adaptability, communication, collaboration, critical thinking, leadership, and empathy. Collaborative engagement with external partners such as industries, schools, and civil society organizations has further enriched student learning experiences. Overall, the MBKM curriculum plays a pivotal role in producing graduates who are creative, innovative, adaptive, and competitive in the global workforce. However, the study also identifies several implementation challenges, including curriculum integration, coordination with external partners, assessment mechanisms, and resource constraints. Based on these findings, the study recommends strengthening the evaluation of student learning outcomes, expanding institutional networks, improving the development of soft skills, and optimizing lecturer and mentor support to ensure the program's sustainability and long-term impact.